Contribution of Learning Facilities Management Practices and Instructors Competency on Learning Outcomes of Students in Seamanship Education Center - Harun, Cut Zahri; Pranata, Wibisana; Niswanto, Niswanto (FKIP Universitas Lampung, 2020)
Contribution of Learning Facilities Management Practies and Instructors Competency on Learning Outcomes of Students in Seamanship Education Center. Objectives: This study aimed to determine the influence of learning facilities and instructor competencies on students’ learning outcomes at Seamanship Education Center of Malahayati Aceh, Indonesia. Methods: This study employed a quantitative approach with correlation techniques and questionnaire as an instrument. Data collection techniques: sampling on a non-probability sampling basis. Research sample is 100 students of the Formation Seafarers Training III Nautical and Technical Department. Findings: The results of this study indicate that: (1) there is a significant influence between learning facilities on student learning outcomes partially; (2) there is a significant influence between instructor competencies on student learning outcomes partially.Keywords: learning outcomes, learning facilities, instructor competency DOI: 10.23960/jpp.v10.i1.202004